To evaluate the expression x(y-9)3+2 when x = 8 and y = 9, we substitute the given values into the expression:
x(y-9)3+2 = 8(9-9)3+2
Since (9-9) equals 0, the expression becomes:
8(0)3+2
Next, we simplify the expression by multiplying 8 by 0:
0 * 3 + 2
Since any number multiplied by 0 is always 0, this simplifies to:
0 + 2
Finally, we add 0 and 2:
0 + 2 = 2
Therefore, when x = 8 and y = 9, the expression x(y-9)3+2 evaluates to 2.
Evaluate the expression when x = 8 and y = 9:
x(y-9)3+2 show your work
1 answer